2018
DOI: 10.1016/j.spinee.2017.08.228
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with the long-term outcome of lumbar spinal stenosis surgery: a 10-year follow-up study

Abstract: Patients with LSS with even slightly elevated depressive symptoms have an increased risk of postoperative pain and disability in a 10-year follow-up. To improve the surgical outcome among these patients, screening for depression both preoperatively and during the rehabilitation following surgery is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 41 publications
(53 reference statements)
2
43
0
Order By: Relevance
“…5 Importantly, the authors noted that while individuals with higher depressive scores demonstrated statistically significant improvement from preoperative ODI scores, observed improvements in VAS and walking distance were not significantly different at 10 years. 5 These results sharply contrast with the significant improvements in all measures observed in the nondepressed cohort in this study. In a review of 67 adults undergoing lumbar discectomy, Chaichana et al noted that individuals with anxiety or depression were significantly less likely to achieve a minimum clinical important difference in disability and quality of life (QOL).…”
Section: Effects Of Psychological Disorders On Postoperative Outcome mentioning
confidence: 94%
See 1 more Smart Citation
“…5 Importantly, the authors noted that while individuals with higher depressive scores demonstrated statistically significant improvement from preoperative ODI scores, observed improvements in VAS and walking distance were not significantly different at 10 years. 5 These results sharply contrast with the significant improvements in all measures observed in the nondepressed cohort in this study. In a review of 67 adults undergoing lumbar discectomy, Chaichana et al noted that individuals with anxiety or depression were significantly less likely to achieve a minimum clinical important difference in disability and quality of life (QOL).…”
Section: Effects Of Psychological Disorders On Postoperative Outcome mentioning
confidence: 94%
“…While this focused research provides a magnitude of knowledge on these 2 disease processes, important gaps in knowledge exist regarding the effects of relatively common psychological diseases, such as schizophrenia and bipolar disorder, on outcomes in spine surgery. Current evidence suggests that patients with psychologic disorders have higher rates of both acute and chronic spine complaints, 3 worse outcomes with treatment, 4 - 6 and more frequent use of narcotic medications. 7 Additionally, those that undergo surgical intervention have higher complication rates than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to increasing the risk of PAD, depression also appears to impact the functional status and symptoms of patients with PAD. Depressive symptoms was associated with functional impairment [28] , greater postoperative disability [29] , and higher mortality rates in patients treated with percutaneous coronary intervention [30] .…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, patients with moderate psychosocial distress have poorer clinical outcomes, although, in comparison to the preoperative baseline, they improved [13]. In a 10-year follow-up after decompression surgery for lumbar stenosis, Tuomainen et al reported that patients with lumbar stenosis with elevated depressive symptoms had an increased risk of postoperative pain and disability in the long term follow-up than patients without depressive symptoms [14].…”
Section: Introductionmentioning
confidence: 99%